Analysis of mammographic findings in a tertiary care hospital of Nepal - Humagain, M; Paudel, S (Journal of Institute of Medicine Nepal, 2015)
Introduction: Mammography is commonly the first line imaging procedure in screening of breast cancer in women. It is also commonly used as diagnostic test in the assessment or characterization of palpable breast mass along with ultrasonography. The purpose of our study was to assess the mammographic findings in women undergoing screening and diagnostic mammography.Methods: This was a prospective cross sectional study analyzing the outcomes of 497 consecutive screen-film mammographic examinations, 369 (74.2%) diagnostic and 128 (25.8%) screening, performed in female patients from 4th July 2012 to 15th October 2012 in Tribhuvan University Teaching Hospital. Analysis was based on the final assessment report of mammogram reviewed by the experienced radiologists following Breast Imaging Reporting and Data System (BI-RADS) classification. BI-RADS score 4, 5 and 6 were considered as positive, BI-RADS score 1, 2 and 3 were considered as negative and BI-RADS score 0 was considered inconclusive requiring additional imaging.Results: The mean age of women was 46.3 years (range 26-83 years). Among 369 cases of diagnostic mammograms 300 (81.3%) were negative, 27 (5.4%) were positive and rest 42 (8.4%) were inconclusive. Among 128 cases of screening mammograms, 117 (91.4%) were negative, 11 (8.6%) were inconclusive and none of them were positive. Among total (497) numbers of mammographic examinations, 417 (84%) were negative, 27 (5.4%) were positive and 53 (10.6%) were inconclusive. BI-RADS 1 was the most common reported finding comprising 26.8% in diagnostic and 12.1% in screening group.Conclusion: Analysis of diagnostic mammography examinations yields different results compared with those of screening examinations, including different patient demographics; higher number of positive findings; and possibly higher cancer detection rates. Diagnostic and screening data should be segregated during record keeping and analysis of combined results should be based on known differences between diagnostic and screening outcomes.